Borates: Surface Plasmon Enhanced Hot Exciton Emission in Deep UV‐Emitting AlGaN Multiple Quantum Wells (Advanced Optical Materials 5/2014). Issue 5 (May 2014) - Yin, Jun; Li, Yang; Chen, Shengchang; Li, Jing; Kang, Junyong; Li, Wei; Jin, Peng; Chen, Yonghai; Wu, Zhihao; Dai, Jiangnan; Fang, Yanyan; Chen, Changqing
<x xml:space="preserve">Abstract</x> Deep UV (DUV) nonlinear optical (NLO) crystals are in urgent demand for harmonic generation with wavelengths between 200 and 150 nm, owing to their core applications in advanced instruments in laser science and technology, including areas such as ultra‐fine spectrum probing, precise micro‐machining, laser cooling, and atto‐second pulse generation. Here, a KBe2BO3F2 crystal and its atomic structure are displayed, and the development prospects of DUV NLO crystals are evaluated by Z. S. Lin, C. T. Chen, and co‐workers based on a structure‐property relationship analysis. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>